Expression of GRP78 and GRP94 proteins in the human micro- and macrovascular endothelial cells under hypoxia - Suhan, Tatyana O.; Nevmerzhitskaya, Aleksandra S. (Experimental Biology and Biotechnology, 2017)
It was investigated the expression of stress activated chaperons GRP78, GRP94 in human microvascular and macrovascular endothelial cells in normoxic and hypoxic conditions of cultivations. The experiments were carried out on HUVEC (human umbilical vein endothelial cells), HDMEC (human dermal microvascular endothelial cells) and HMPEC (human microvascular placental endothelial cells). The proteins expression was estimated with immunoblotting. Densitometry of the immunoblotting results was done with «ImageJ» software. It was find out that in normoxic conditions pattern of GRP78 and GRP94 expression in HUVEC is similar to HDMEC and differs from HMPEC. Hypoxia changes expression of stress-induced proteins GRP78 and GRP94. Expression of GRP78 and GRP94 in microvascular endothelial cells (HDMEC, HMPEC) differs from expression in macrovascular endothelial cells (HUVEC).